Effect of Fiber Post-Resin Matrix Composition on Bond Strength of Post-Cement Interface - Ibtisam O. M. Alnaqbi; Haitham Elbishari; Emad S. Elsubeihi (International Journal of Dentistry)
Objective. To evaluate the influence of 3 different post-resin matrix systems cemented with dual-cure resin cement in simulated root canals made of PMMA acrylic sheet. Methods. 3 types of fiber posts (n = 60) with different resin matrixes divided into 3 groups: group 1 cross-linked FRC Postec Plus post (n = 20), group 2 cross-linked Rely X post (n = 20), and group 3 Interpenetrated IPN Everstick post (n = 20). All posts were cemented using Multilink Automix dual-cure cement. Posts were cemented into acrylic blocks in order to purely test the strength of cement-post interface. After one week storage at 37°C, two sections of 1 mm thickness from middle-third were subjected to micro-push-out test at crosshead speed 0.5 mm/min. Results. The data were analyzed using one-way analysis of variance (ANOVA). The variable fiber post-matrix system was found to significantly affect the push-out bond strength (p<0.001). Group 2 exhibited that the highest mean push-out bond strength was (5.36 + 2.3 MPa), and group 3 showed the lowest mean push-out (0.41 + 0.4 MPa). There was significant difference among the groups regarding the failure mode as chi-square test revealed (p<0.001). Conclusion. Prefabricated cross-linked posts with epoxy-based matrix demonstrated higher bond strength than prefabricated cross-linked posts with Bis-GMA-based matrix and posts with semi-IPN matrix when luted with dimethacrylate-based dual-cured resin cement.